(untitled) (Research, Society and Development, 2021)
This article aims to characterize management and performance profiles of Civil Society Organizations (CSOs) formed in networks aimed at social development. A case study analyze 20 CSOs comparatively, taking as starting point analytical dimensions related to the planning and execution of activities, direction and control, and selection of members to compose the organization. The study identifies that the performance of CSOs can be understood from two parameters: (i) strategic governance, that is, the political influence of the organization, whose focus is on raising awareness and mobilizing a target audience for a given cause; and (ii) grassroots performance, that is, the performance of organizations in the implementation of programs, projects and/or actions at street level or in loco. Based on these parameters, a theoretical-conceptual matrix that categorizes the performance of CSOs in four profiles is proposed: Regulatory Profile; Inaccurate profile; Hybrid Profile; and Frontline Profile. The matrix can serve as a tool for a more efficient distribution of resources by the State, identifying CSOs that are endowed with the characteristics that will provide better capillarity and efficiency to provide the desired service. The ability of a government to recognize the profile of CSOs operating in its territory allows it to outline arrangements that strengthen its performance. Therefore, the findings stimulate theoretical reflections and empirical investigations that expand knowledge about the phenomenon, opening up possibilities for studies on networks in different perspectives and contexts.